Analysis of the SAR distributions in three-layered bio-media in direct contact with a water-loaded modified box-horn applicator - Gupta R.C.; Singh S.P. (My University, 2025)
This paper presents theoretical analysis of the specific absorption rate (SAR) distribution in three-layered bio-media (skin, fat, and muscle layers) in direct contact with a modified box-horn applicator in which the horn is flared in both the E- and H-planes for hyperthermia treatment of cancer. The modified box-horn is assumed to be filled with water to provide a better impedance match to the bio-media. The present analysis is based on a plane-wave spectral technique. The spatial distribution of SAR in skin, fat, and muscle layers are computed and presented at 433 and 2450 MHz. Higher SAR value in each of the bio-layers, higher penetration depth, and lower resolution in the muscle layer are observed at 433 MHz in comparison to those at 2450 MHz for the water-loaded modified box-horn. The effect of substituting a pyramidal horn in place of an H-plane sectoral horn in the design of the box-horn on the SAR distribution is also examined. The results have been validated against published results in the literature. © 2005 IEEE.